Oral health promotion efficiency in the control of oral biofilm - Nélio Jorge Veiga; Patricia Carvalho; Octávio Ribeiro; Inês Coelho (Universidade de Fortaleza, 2014)
Objective: To assess the efficacy of oral health instructions, particularly in the control of dental plaque, as well as assess the effectiveness of the reinforcement of the same instructions. Methods: A quasi-experimental study was conducted at the University Clinic of the Portuguese Catholic University (UCP) in Viseu-Portugal from January to June 2012. Three different assessments were performed with 30 participants using the O'Leary Plaque Index and a questionnaire on oral health behavior, with a one-month interval between each assessment. In the first assessment, all participants received the same instructions of oral hygiene and the O'Leary Plaque Index registration and the application of the questionnaire were performed; in the second assessment, a new registration of the O'Leary Index was made, but only the experimental group (n=16) received the reinforcement of oral health instructions, and in the third assessment, a new registration of the O'Leary Plaque Index was made for all the individuals (n=30). Results: Both control and experimental groups showed a decrease in the O'Leary Plaque Index, but the latter showed a more significant decrease in the last assessment: 38.19% (n=16) vs. 69.57% (n=14), p <0.05. Regarding the frequency of toothbrushing, in the experimental group, 68.8% (n=11) brushed the teeth at least twice a day, while in the control group only 57.1% (n=8) performed the same frequency of toothbrushing. In this case, statistically significant differences were found between the two groups (p<0.05). Conclusion: Oral health promotion through oral hygiene instruction was effective in improving oral health behaviors, and, consequentely, the control of dental biofilm. doi:10.5020/18061230.2014.p117